AN EFFECTIVE AGRICULTURAL STRUCTURE DEVELOPMENT OF AGRO-INDUSTRIAL HOLDING THESIS PROJECTS - Li, Dmitriy (Nazarbayev University Graduate School of Business, 2016)
Kazakhstan is an agro industrial country and one of the largest grain powers in the world. The area of grain crops is more than eighteen million hectares including twelve million hectares for wheat crops, which provide approximately six thousands tons of gross harvest annually. Another six million hectares are for crops such as corn, rice, oats, barley, buckwheat, cotton, sunflower, fruits, and vegetables...
Thesis
Keywords: private agricultural holding; Financial and economic analysis; agricultural sector; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Agricultural history